Fabrication of patient specific composite orbital floor implants by stereolithography. (10th September 2015) - Geven, Mike A.; Varjas, Viktor; Kamer, Lukas; Wang, Xinjiang; Peng, Jiang; Eglin, David; Grijpma, Dirk W.
Abstract : Fractures of the orbital floor are common in traffic accidents and assaults, and inadequate treatment can result in serious complications. Accurate anatomical reconstruction of the orbit using implants is the preferred treatment. Implants require degradability, adequate mechanical properties to support the orbital contents, and osteoinductivity or osteoconductivity so that the implant is replaced by de novo bone over time. Here, we report on a semi‐automatic process for the generation of virtual models of patient‐specific implants for orbital floor reconstruction. These models were generated using clinical computed tomography images of five clinical cases of orbital fracture. To fabricate accurately shaped implants based on the models, we utilized stereolithography, a high‐resolution additive manufacturing technique. We prepared resins from bioresorbable, photo‐curable functionalized poly(trimethylene carbonate) oligomers and osteoinductive nano‐hydroxyapatite to manufacture composite implants. Incorporation of 40 wt.% nano‐hydroxyapatite into photo‐crosslinked poly(trimethylene carbonate) leads to an increase of the E modulus, ultimate strength and toughness from 2.8 to 60 MPa, 2.4 to 7.1 N/mm2 and 330 to 1671 N/mm2, respectively. Additionally, water uptake increased from 0.8% to 7.3%, and water contact angle decreased from 80° to 68°. Patient‐specific, homogeneous, and mechanically stable implants can readily be prepared using these composite resins. Copyright © 2015 John Wiley & Sons, Ltd.